2005
DOI: 10.1074/jbc.m502209200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Autoregulatory Function of Hepatitis B Virus M Protein on Surface Gene Expression

Abstract: The hepatitis B virus surface gene consists of a single open reading frame divided into three coding regions: pre-S1, pre-S2, and S. By alternate translation at each of the three initiation codons, L, M, and S proteins can be synthesized. Studies have shown that M protein is not essential for viral replication, virion morphogenesis, or in vitro infectivity. In this study, we show that native M protein can regulate surface gene expression at the transcriptional level. The regulatory effect of M protein is media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…We therefore explored the potential role of preS2 as a transcriptional activator of hTERT. Using preS2 fused with EGFP tag, we confirmed the nuclear localisation of preS2 (fig 3A), as reported previously 32. To test whether preS2 can act as a transcriptional activator, we co-transfected preS2 and luciferase reporters and observed the preS2-mediated upregulation of hTERT promoter activity in different cell lines, including immortal liver cell line LO2, HCC cell lines Bel7402 and HepG2, and African green monkey kidney cell line COS-7 (fig 3B).…”
Section: Resultssupporting
confidence: 85%
“…We therefore explored the potential role of preS2 as a transcriptional activator of hTERT. Using preS2 fused with EGFP tag, we confirmed the nuclear localisation of preS2 (fig 3A), as reported previously 32. To test whether preS2 can act as a transcriptional activator, we co-transfected preS2 and luciferase reporters and observed the preS2-mediated upregulation of hTERT promoter activity in different cell lines, including immortal liver cell line LO2, HCC cell lines Bel7402 and HepG2, and African green monkey kidney cell line COS-7 (fig 3B).…”
Section: Resultssupporting
confidence: 85%
“…Huang et al . defined a novel regulatory role of M protein, which may undergo a proteolytic process to generate a MHBs au species to up‐regulate the transcription of S promoter . It is possible that disrupting the synthesis or deleting part of the M protein would lose the enhancement and result in changing the ratio of L vs. S and accumulation of L protein in ER.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggested that M protein is not essential for viral repli- Table 4. Functional mapping of pre-S deletion mutants from chronic carriers (CC) and hepatocellular carcinoma (HCC) patients (37). It is possible that disrupting the synthesis or deleting part of the M protein would lose the enhancement and result in changing the ratio of L vs. S and accumulation of L protein in ER.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have suggested that M protein is not essential for viral replication, virion morphogenesis, or infectivity. Huang et al[ 40 ] defined a novel regulatory role for M protein, which may undergo a proteolytic process to generate an MHBs au (aa 1-57 of M protein) species to upregulate the transcription of S promoter. In addition, the pre-S2 region of M protein binds to pHSA (aa 3-16), but the significance of this binding is unknown[ 34 ].…”
Section: The Biological Function Of the Pre-s/s Regionmentioning
confidence: 99%